Description and Classification of Tempering Materials Present in Pottery Using Digital X-Radiography - Alan Nagaya; Oscar G. de Lucio; Soledad Ortiz Ruiz; Eunice Uc González; Carlos Peraza Lope; Wilberth Cruz Alvarado (NDT)
Archaeological pottery X-radiography is mainly used for two applications: fabric characterization and identification of forming techniques. Both applications require imaging of tempering materials and other additives. With digital X-radiography, it is easy to enhance the image to compute and characterize these materials. In this study, a combination of ImageJ plug-ins such as “threshold”, “analyze particles”, and “fit polynomial” were used to describe tempering materials of a set composed of archaeological pottery sherds. It was found that two different types of tempering materials were used. The first type was characterized by a grain size of less than 0.5 mm and no well-formed particles. In contrast, the second group had a grain size larger than 0.5 mm and well-formed particles.